SPECT/CT with 99mTc labelled heat-denatured erythrocyte to detect thoracic and abdominal splenosis. : SPECT/CT with 99mTc labelled heat-denatured erythrocyte - Graziani, Tiziano; Baldari, Giorgio; Sammartano, Antonino; Scarlattei, Maura; Migliari, Silvia; Pescarenico, M. Giovanna; Cidda, Carla; Bola, Stefano; Ruffini, Livia (Acta Biomedica Atenei Parmensis, 2020)
Scintigraphy with 99mTc labelled heat-denatured erythrocyte (DRBC) allows non invasive diagnosis of heterotopic splenic tissue implantation (splenosis) following splenic trauma or surgery. Single-photon emission computed tomography (SPECT) combined with computed tomography (CT) improves diagnostic accuracy of planar imaging through a more precise localization of functional findings. We report about two cases of splenosis occurring many years after splenectomy. 99MTc-DCRBC scintigraphy was used for differential diagnosis of metasttic disease in one case and to assess an incidental finding at bone scan in the second one. SPECT/CT increased specificity of planar imaging, expecially revealing combined (thoracic and abdominal) splenosis.